2022
DOI: 10.1001/jamanetworkopen.2022.15934
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Postvaccination Breakthrough COVID-19 Infections Among Adults With HIV in the United States

Abstract: Key Points Question Are the rate and risk of COVID-19 breakthrough infections higher among vaccinated people with vs without HIV in the United States through December 31, 2021? Findings In this cohort study of 113 994 patients, risk of breakthrough infection was low overall (3.8%) but 28% higher in people with vs without HIV. The breakthrough rate was also higher in people with vs without HIV (55 cases per 1000 person-years vs 43 cases per 1000 person-years… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 34 publications
6
50
0
Order By: Relevance
“…Furthermore, given the safety of the mRNA vaccines, the overall lower vaccine-inducible antibody response observed in PLWH, the observed waning of serum antibody levels over time, and immune escape by VOCs, we think that providing additional vaccinations to all PLWH may optimise protection. Some recent studies confirm that a third dose in PLWH is beneficial and important in light of more frequent breakthrough infections in PLWH after vaccinations [ 36 , 37 ]. Based on these results, an argument can be made for prioritisation and use of a more targeted approach in, for example, older PLWH, in those with lower CD4+ T-cell counts, or based on measured antibody responses and neutralisation capacity after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the safety of the mRNA vaccines, the overall lower vaccine-inducible antibody response observed in PLWH, the observed waning of serum antibody levels over time, and immune escape by VOCs, we think that providing additional vaccinations to all PLWH may optimise protection. Some recent studies confirm that a third dose in PLWH is beneficial and important in light of more frequent breakthrough infections in PLWH after vaccinations [ 36 , 37 ]. Based on these results, an argument can be made for prioritisation and use of a more targeted approach in, for example, older PLWH, in those with lower CD4+ T-cell counts, or based on measured antibody responses and neutralisation capacity after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] In the event of a breakthrough infection, vaccination will reduce the severity of the illness and lower the likelihood of acquiring COVID-19. 16,[34][35][36] The safety of delivering the currently available SARS-CoV-2 vaccines before, during, and after pregnancy is supported by all available research. 37,38 However, vaccine hesitancy becomes one of the greatest challenges globally.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that people living with immunocompromised conditions, such as HIV infection, have worse outcomes after SARS-CoV-2 infection than immunocompetent individuals [41,42]. This observation has also been con rmed in an immunosuppressed preclinical model of SARS-CoV-2 infection [43].…”
Section: Discussionmentioning
confidence: 80%